Arena size modulates functional responses via behavioral mechanisms. (21st December 2018) - Uiterwaal, Stella F; Dell, Anthony I; DeLong, John P
Abstract: Laboratory-based functional response experiments, in which foraging rates are measured across a range of resource densities, are central for determining trophic interaction strength. Historically these experiments often are performed in arbitrarily sized arenas, with larger sized organisms generally used in larger arenas. However, arena size influences foraging rates and therefore also estimates of the functional response parameters, particularly space clearance rate (attack rate). We hypothesized that nonrandom movement within arenas by predators and prey may explain this effect. To test this hypothesis, we video-recorded Schizocosa ocreata wolf spiders (predators) and flightless Drosophila melanogaster prey in circular arenas of 3 different sizes to reveal thigmotactic behavior. We then estimated foraging rates and space clearance rates from feeding trials performed at a single, low prey density in 3 differently-size arenas in either annular (ring-shaped) or circular arenas. Annular arenas mitigated the effects of predator and prey aggregation and thus controlled the experienced prey density near arena edges. Unlike the circular arenas, annular arenas produced similar foraging rates and space clearance rate estimates across arena sizes, confirming that it is the increased density of prey along edges that generates the previously observed arena size effect. Our results provide a key insight into how animal behavior and experimental design must be considered for the accurate interpretation of foraging rates, both when considering standalone functional responses and when making comparisons across experiments. Abstract : Many animals prefer to be near walls or other physical objects, known as thigmotaxis. However, predation experiments traditionally do not consider this. We show that wolf spider predators and fruit fly prey exhibit thigmotaxis in the lab, and that the accuracy of predation experiments is improved by accounting for this behavior.